Atlas of Swept Source Optical Coherence Tomography - Michalewska, Zofia; Nawrocki, Jerzy (Springer International Publishing : Imprint: Springer, 2017)
This atlas presents an overview of Swept Source Optical Coherence Tomography (OCT) and its implications on diagnostics of vitreous, retina and choroid. As the sensitivity of OCT imaging devices has increased, updated technologies have become available for engineers, scientists and medical specialists to adopt, and recent developments have led to the creation of a new generation of devices. The aim of this resource is to explain this new technology and its advantages over previous imaging devices and to illustrate how it may be used in to define eye diseases, aid in their treatment and facilitate treatment options.
Keywords: Medicine.; Ophthalmology.; elektronické knihy; electronic books